Morphological Identification of Sandflies and Their Species’ Diversity - Baharshahi, Amin; Behravan, Mahmoodreza; Keikhosravi, Alireza (Archives of Advances in Biosciences, 2019)
L Introdaction:Leishmaniasis is a zoonosis disease, presented in three forms including cutaneous, mucocutaneous, and visceral (kala-azar). The parasite, Leishmania spp, is transferred by the causative agent of the disease, namely the sand-fly. Accurate identification of sand-flies helps to prevent and treat the disease. Materials and Methods:This study was conducted to identify sand-fly species distributed in Birjand, east of Iran. Sand-flies were collected from different parts of Birjand city, Iran through using sticky traps in summer 2015. Captured female specimens were mounted and identified by specific keys. Result:In this study, a total of 1480 samples of sand-flies were collected, out of which 945 sand-flies in areas were related to animal and 535 sand-flies in areas related to human. The most prevalent species, among 654 collected female specimens were Phlebotomus sergenti (22.17%) and Sergentomyia dentata (49.54%). Conclusion:According to the current results, the dominant species among disease vectors of cutaneous leishmaniasis is the urban type. Because of the presence of Leishmania tropica, the city's health system must take necessary care to control cutaneous leishmaniasis.